Implementasi Algoritma Shortest Job First dan Round Robin pada Sistem Penjadwalan Pengiriman Barang - Monica Santika; Seng Hansun (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2014)
Delivery of goods will normally be conducted in accordance with the queuing time of booking. Sometimes, it is inefficient and results in a delay on the delivery of goods. Therefore, to make a better scheduling system, the Shortest Job First and Round Robin algorithms been implemented. From the results of experiments, Shortest Job First and Round Robin algorithms successfully applied to the scheduling delivery application. Shortest Job First algorithm is better than Round Robin scheduling in the case of delivery of goods, because the algorithm execution process which takes small time will be moved before the process which takes much time, so it needs smaller time than using Round Robin algorithm. Index Terms - Round Robin, Scheduling, Shipping, Shortest Job First